Genotyping markers used for multi locus VNTR analysis with ompA (MLVA-ompA) and multi sequence typing (MST) retain stability in Chlamydia trachomatis - Labiran, Clare; Clarke, Ian N.; Cutcliffe, Lesley T.; Wang, Yibing; Skilton, Rachel J.; Persson, Kenneth; Bjartling, Carina; Herrmann, Björn; Christerson, Linus; Marsh, Peter (Frontiers in Cellular and Infection Microbiology, 2012)
We aimed to evaluate the stability of the Chlamydia trachomatis MLVA-ompA and MST typing systems through multiple passages in tissue culture. Firstly, we analysed the stability of these markers through adaptation of C.trachomatis to tissue culture and secondly we examined the stability of a four-locus MLVA-ompA and a five-locus MST system after multiple passages in tissue culture. Marker sequences were monitored through successive chlamydial developmental cycles to establish the stability of the individual DNA markers through many bacterial divisions and this, in turn, informed us of the usefulness of using such typing systems for short and long term molecular epidemiology. Southampton genitourinary clinic (GUM) clinic isolates from endocervical swabs collected from women who had contracted C.trachomatis were passaged through tissue culture. MLVA-ompA typing was applied to primary swab samples and to the same samples after C.trachomatis had been adapted to cell culture (eight passages). Sequence data from time zero and passage-eight isolates were aligned with reference sequences to determine the stability of the markers. The Swedish new variant (nvCT) underwent 72 passages in cell culture and the markers of the two schemes were similarly analysed. Analysis of genetic markers of MLVA-ompA before and after the isolates were introduced to tissue culture showed no change in sequence. The nvCT that had been passaged 72 times over the duration of a year also showed no variation in the sequence for both the genotyping schemes. MLVA-ompA and MST markers are stable upon adaptation of C.trachomatis to tissue culture following isolation of strains from primary endocervical swab samples. These markers remain stable throughout multiple rounds of cell-division in tissue culture, concomitant with the incubation period and appearance of symptoms normally associated with host - infection. Both genotyping schemes are suitable for short- and long-term epidemiology of C.trachomatis.